Contextualizing Relative Sea-Level Rise in Boston Harbor: A Geological Reconstruction from Short Beach Marsh, Boston, Massachusetts - Gleason, Caroline (Tufts Archival Research Center, 2019)
Relative sea level (RSL) varies spatially and temporally, and therefore must be studied through two lenses: a spatial lens, using RSL at a particular location; and a temporal lens, using past RSL to contextualize modern sea-level trends. Sea-level rise over the next century (and beyond) threatens coastal cities around the world with more frequent flooding during high tides and storms. This study focuses on modern and past RSL rise in Boston Harbor, taking advantage of its long tide-gauge record, which during the 20th century recorded a rate of RSL that was higher than the rate of global mean sea-level (GMSL) rise. To determine whether the rate of modern RSL rise in Boston is unusual, I put that rate in the context of RSL trends during the previous ~4000 years using geologic data from a salt marsh at Short Beach in Boston, Massachusetts. Based on radiocarbon dating and analysis of salt-marsh foraminifera, I generated six sea-level index points that constrain the elevation of RSL through time. I found that the rate of RSL rise increased from ~0.6 mm yr-1 over the past ~4000 years to ~2.8 mm yr-1 in the last century. My results indicate that this change was driven by an increase in eustatic influence on RSL from ~0 mm yr-1 to ~2.2 mm yr-1, particularly from ocean thermal expansion and glacier mass loss.